Effects of different photoperiods and feeding regimes on immune response, oxidative status, and tissue damage in juvenile rainbow trout (Oncorhynchus mykiss) - Xu, Hanying; Shi, Ce; Ye, Yangfang; Mu, Changkao; Wang, Chunlin (Frontiers in Marine Science, 2022)
A three-month culture experiment was conducted to investigate the effects of the feeding regime on liver health, non-specific immunity, and apoptosis of juvenile rainbow trout under constant light conditions. A total of six experimental groups contained two photoperiods [LL (24L:0D) and LD (12L:12D)] and three feeding regimes [R (random feeding), D (mid-dark stage feeding), L (mid-light stage feeding)], defined as R-LL, D-LL, L-LL, R-LD, D-LD, L-LD. The experiment results revealed a significantly higher alanine aminotransferase (ALT) level in the nocturnal feeding group (D-LD) and significantly higher aspartate aminotransferase (AST) in the R-LL and D-LL groups, indicating possible liver damage in these groups. In addition, high serum levels of immunoglobulins M (IgM), complement 3 (C3), and complement 4 (C4) were observed in the LL (compared to LD), R (LL conditions), and D (LD conditions) groups, suggesting that stress may be present in these groups. Meanwhile, under LL, high cytokine genes (tnf-α, il-1β, il-6, and il-8) expression were observed in the liver and intestine of the L group, possibly reflecting a stronger immune response. In the liver, high malondialdehyde (MDA) content was observed in the LL (compared to LD), R (LD conditions), and D (LL conditions) groups, suggesting that these groups were subjected to oxidative damage. Further, higher apoptosis genes (cytc and bcl-2) expression in the liver was detected in the R and D-LD groups. The highest level of hepatic apoptotic cells was also observed in the D-LD group. Taken together, long-term exposure to LL, random feeding, and nocturnal feeding can cause oxidative damage to juvenile rainbow trout, leading to hepatocyte apoptosis, while scheduled diurnal feeding can alleviate the oxidative damage caused by LL.